Integrating human and ecological dimensions: The importance of stakeholders' perceptions and participation on the performance of fisheries co-management in Chile. - Milagros Franco-Meléndez (Public Library of Science (PLoS), 2021)
Increasing attention is paid to the interdependence between the ecological and human dimensions to improve the management of natural resources. Understanding how artisanal fishers see and use the common-pool resources in a co-management system may hold the clue to establishing effective coastal fisheries policies or strengthening existing ones. A more comprehensive planning of the system will also have a bearing on how to reduce conflicts and strengthen social networks. We surveyed artisanal fishers and decision-makers to determine their perceptions about the Management and Exploitation Areas of Benthic Resources (known as MEABR) in Chile's Biobio region. We performed a field study from November 2018 to August 2019, applying a set of questionnaires to determine the ecological and human attributes that contribute to MEABR outcomes, and then constructed composite scores for those attributes according to a multidimensional scaling technique ("Rapfish"). We find that fishers have different perspectives: surprisingly, women highlighted that the institutional dimension was the most influential on MEABR performance, whereas men highlighted the ecological and economic outcomes. The decision-makers' role in the MEABR system was considered adequate, but communication and socialization of regulations were irregular. Results also showed that fishers expressed dissatisfaction with illegal fishing practices (poaching), productivity, profits, and conflicts inside and outside the MEABRs. Our study allowed us to better understand how the MEABR has developed in the region. We recommend strengthening local management strategies with particular attention paid to networking among stakeholders, including gender inclusive relationships.